2019
DOI: 10.1186/s12893-019-0630-5
|View full text |Cite
|
Sign up to set email alerts
|

Spine surgeon specialty differences in single-level percutaneous kyphoplasty

Abstract: BackgroundPercutaneous kyphoplasty (PKP) is a procedure performed by a spine surgeon who undergoes either orthopedic or neurosurgical training. The relationship between short-term adverse outcomes and spine specialty is presently unknown. To compare short-term adverse outcomes of single-level PKP when performed by neurosurgeons and orthopedic surgeons in order to develop more concretely preventive strategies for patients under consideration for single-level PKP.MethodsWe evaluated patients who underwent single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…To our knowledge, there are no previous studies comparing the outcomes of orthopedic surgeons and neurosurgeons performing cement augmentation procedures using a large cohort of patients. We found no difference between the outcomes of the various populations with regards to operator specialty training, consistent with prior studies indicating no differences between the groups [ 30 ]. Similar results have been reported with regards to elective lumbar and cervical spine procedures as well [ 31 - 33 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, there are no previous studies comparing the outcomes of orthopedic surgeons and neurosurgeons performing cement augmentation procedures using a large cohort of patients. We found no difference between the outcomes of the various populations with regards to operator specialty training, consistent with prior studies indicating no differences between the groups [ 30 ]. Similar results have been reported with regards to elective lumbar and cervical spine procedures as well [ 31 - 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…We found no difference between the outcomes of the various populations with regards to operator specialty train- ing, consistent with prior studies indicating no differences between the groups. 30 Similar results have been reported with regards to elective lumbar and cervical spine procedures as well. [31][32][33] There are several limitations to the current study.…”
Section: Figsupporting
confidence: 80%
“…Of 10 studies that compared complications, 8 (80.0%)8–12,20,21,25 found no difference in complication rates between subspecialties 8–12,20–22,25,26. Mabud et al 22 found a lower overall complication rate for orthopedics for lumbar fusions (14.5% vs .…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies reported on readmission rates after surgery 3,4,7,8,10,11,19,21–23. Eight did not detect differences in readmission rates 7,8,10,11,19,21–23. Of the studies that did detect differences based on surgical subspecialty, one was a database study (NSQIP) comparing anterior lumbar interbody fusions (ALIFs) and lateral lumbar interbody fusion, which found lower readmission rates among neurosurgeons for multilevel procedures (3.9% vs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation